Transcription factor VvibHLH93 negatively regulates proanthocyanidin biosynthesis in grapevine - Cheng, Jing; Shi, Ying; Wang, Jun; Duan, Changqing; Yu, Keji (Frontiers in Plant Science, 2022)
Proanthocyanidins (PAs) derived from grape berries determine the astringency and bitterness of red wines. The two leucoanthocyanidin reductases (VviLAR1 and VviLAR2) are crucial for PA accumulation in grapevine. Our previous studies show that the promoter of VviLAR1 contains multiple proposed bHLH transcription factor binding sites, but the corresponding bHLH family regulators remain unknown. Here we identified and functionally characterized VvibHLH93 as a new bHLH transcription factor in PA pathway. Yeast one-hybrid and electrophoretic mobility shift assays showed that VvibHLH93 bound the E/G-box in VviLAR1 promoter. And VvibHLH93 gene was mainly expressed in grape flowers, tendrils, stems and berries at PA active stages. Overexpression of VvibHLH93 suppressed PA accumulation in grape callus, which was linked to the repression of the transcript levels of two VviLARs. The gene expression analysis in transgenic grape callus and the dual-luciferase assay in tobacco leaves together revealed that VvibHLH93 targeted a broad set of structural genes and transcription factors in flavonoid pathway. This research enriches the regulatory mechanism of the two VviLAR genes, and provides new insights into regulating PA content in grape berries.